2006
DOI: 10.1177/0192513x06289647
|View full text |Cite
|
Sign up to set email alerts
|

Recollections of Being Loved

Abstract: This study examined the extent to which young adults' recollections of their childhood experiences with parents were associated with their reported feelings and behavior in romantic relationships. Participants were 205 young adults. Based on a question from the Adult Attachment Interview (George, Kaplan, & Main, 1996), participants wrote adjectives that described their childhood relationships with each parent as well as childhood incidents that illustrated those adjectives. Participants' feelings and behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The current findings are consistent with several previous studies (Black & Schutte, 2006;Miller & Hoicowitz, 2004;Pascuzzo et al, 2013;Roisman et al, 2005;Walper & Wendt, 2015) that found that representations of relationships with parents predicted changes in representations of relationships with romantic partners, and are consistent with Crowell et al (2002), who found the reverse. Most of the previous studies either found similar effects for relationships with mothers and fathers, or did not differentiate them.…”
Section: Discussionsupporting
confidence: 92%
“…The current findings are consistent with several previous studies (Black & Schutte, 2006;Miller & Hoicowitz, 2004;Pascuzzo et al, 2013;Roisman et al, 2005;Walper & Wendt, 2015) that found that representations of relationships with parents predicted changes in representations of relationships with romantic partners, and are consistent with Crowell et al (2002), who found the reverse. Most of the previous studies either found similar effects for relationships with mothers and fathers, or did not differentiate them.…”
Section: Discussionsupporting
confidence: 92%
“…Past studies, however, suggest the plausibility of this mechanism particularly among young fathers in emerging adulthood. For example, young adults who reported having loving relationships with their fathers in childhood were more likely to seek comfort from close relationships (Black & Schutte, 2006), whereas distant fatherchild relationships have been linked to greater feelings of relationship anxiety (Seiffge-Krenke, Overbeek, & Vermulst, 2010). In turn, men with relational schemas that promote close, trusting relationships with other adults are more likely to engage in sensitive www.FamilyProcess.org 168 / FAMILY PROCESS parenting and form high-quality relationships with their young children (McFarland-Piazza, Hazen, Jacobvitz, & Boyd-Soisson, 2012).…”
Section: Relational Schemas As a Mechanism Underlying Intergenerationmentioning
confidence: 99%
“…Rewarding relationships with caregivers provide security and a source of meaning and happiness, while separation and loneliness constitute potential risk factors for psychopathology through social isolation [41]. Secure attachment relationships in childhood provide a mechanism for the development of emotional regulation, therefore influencing social relationships in later life [26, 39, 42, 43]. Insecure or avoidant attachment may reduce psychological wellbeing, and lead to attempts to soothe past traumas with polysubstance use [29, 44].…”
Section: Discussionmentioning
confidence: 99%